Shade increases crop yields - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Planting crops under trees in the hot, dry Sahelian zone of Western Africa increases their yields and, because of the micro-climate under the trees, widens the farmer's choice of crop to be planted. Researchers at the International Crops Research...